2016
DOI: 10.1111/jace.14481
|View full text |Cite
|
Sign up to set email alerts
|

Electromechanical Response of Polycrystalline Barium Titanate Resolved at the Grain Scale

Abstract: Ferroic materials are critical components in many modern devices. Polycrystalline states of these materials dominate the market due to their cost effectiveness and ease of production. Studying the coupling of ferroic properties across grain boundaries and within clusters of grains is therefore critical for understanding bulk polycrystalline ferroic behavior. Here, three-dimensional X-ray diffraction is used to reconstruct a 3D grain map (grain orientations and neighborhoods) of a polycrystalline barium titanat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 57 publications
0
6
1
Order By: Relevance
“…In this respect, piezoresponse force microscopy (PFM) and transmission electron microscopy (TEM) disclosed clustering during polarization reversal which ranges from a few [40] to 10 2 -10 3 grains [41,42] in polycrystalline thin films. In contrast to the latter results, in bulk ceramics the grain-resolved three-dimensional X-ray diffraction revealed a collective dynamics at a scale of about 10-20 grains [43][44][45] that roughly corresponds to the next neighbors. The study of polarization and electric field correlations by means of the self-consistent mesoscopic switching model (SMS) [46][47][48], revealed that the electric fieldmediated correlations in bulk ceramics have a typical scale of a grain size.…”
Section: B Polarization Variation Due To Multi-step Switching Events In Uniform Media (Msm Model)contrasting
confidence: 81%
“…In this respect, piezoresponse force microscopy (PFM) and transmission electron microscopy (TEM) disclosed clustering during polarization reversal which ranges from a few [40] to 10 2 -10 3 grains [41,42] in polycrystalline thin films. In contrast to the latter results, in bulk ceramics the grain-resolved three-dimensional X-ray diffraction revealed a collective dynamics at a scale of about 10-20 grains [43][44][45] that roughly corresponds to the next neighbors. The study of polarization and electric field correlations by means of the self-consistent mesoscopic switching model (SMS) [46][47][48], revealed that the electric fieldmediated correlations in bulk ceramics have a typical scale of a grain size.…”
Section: B Polarization Variation Due To Multi-step Switching Events In Uniform Media (Msm Model)contrasting
confidence: 81%
“…1(b), because the possible polarizations of grains are specified by their crystallographic orientations, which are randomly distributed. Additionally, in bulk polycrystals, domains can interact across grain boundaries leading to longer length-scale coupling of domain dynamics [30,31,59]. The c-axis directional distribution should be taken into account and the simplified formula for ∆𝑆 𝑚𝑎𝑥 has to be generalized to ∆S max_real = (Q 12 − Q 11 )P s 2 < (sin 2 θ) > 𝑚𝑎𝑥 (26) where < sin 2 θ > 𝑚𝑎𝑥 defines a maximum possible value for (P 𝑥 2 + 𝑃 𝑦 2 )/P s 2 compatible with the tetragonal symmetry of grains when polarization tries to avoid z-direction.…”
Section: Analysis and Discussion Of Experimental Resultsmentioning
confidence: 99%
“…Thus, the switching of different regions in a ceramic can still be considered as statistically independent with regard to electrical interactions. Correlations in polarization switching, observed between tens of grains in bulk samples [30,31] or up to thousand grains in films [32][33][34], seem to be related to the elastic rather than to the electric interactions. Therefore, the original definition of different regions has to be extended to take elastic interactions into account.…”
Section: Introductionmentioning
confidence: 99%
“…For completeness applications of 3DXRD to minerals (Borthwick et al, 2012;Hall and Wright, 2015;Sørensen et al, 2012a), deep earth science (Nisr et al, 2014(Nisr et al, , 2012Rosa et al, 2015), nuclear materials (Brown et al, 2014;X. Zhang et al, 2015), superalloys (Sedmák et al, 2016) and ferroelectrics Majkut et al, 2016;Varlioglu et al, 2010) should also be mentioned.…”
Section: Introductionmentioning
confidence: 99%